Balkan Migration Crisis and its Impact on Tourism - Koščak, Marko (2017)
This paper attempts to quantify, understand and analyse the effect of the migrant flows upon tourism destinations, considering the funnel theory, as a system, focusing on the beginning (inputs), through (throughput) and at the end of the funnel (outputs). Empirically, the research examines three key questions: 1. Importance of tourism economically to countries in the West Balkan Migrant Corridor; 2. Intensive nature of tourism for these countries; 3. Socio-economic consequences of the migrant flows. The crisis and its effects on tourism looks at a funnel that transmits migrants from the Aegean Sea through the West Balkans to North-West Europe. Importantly, the funnel crisis points are in Greece (beginning) and in Germany (end); the intermediate problem areas (Macedonia, Serbia, Croatia, Slovenia) have been in the throughput of the migrants through the funnel. It must also take account of the security situation in Turkey as well as the difficulty of EU member states in assimilating migrants on the route. Based on the results of the research conducted to date, with the sectional sample data from 2014-2017, it is possible to affirm that the migration crisis in West Balkans countries and countries connected to the migrant corridor has impacted only marginally on tourism. However, This problem is socioeconomic yet deeply humanitarian; whilst unfortunate to reduce a deeply disturbing human issue, such an analysis of “people-flows through the funnel” allows an attempt to quantify, understand and analyse the effect of the migrant flows upon tourism destinations.